(untitled) (Bangladesh Journal of Animal Science, 2014)
The present study was conducted to investigate the feasibility of using coconut milk by replacing reconstituted skim milk for Dahi manufacturing. Reconstituted skimmed milk was replaced by 0, 10, 20, and 30% coconut milk to produce Dahi designated as A, B, C and D. All the samples were analyzed for organoleptic, chemical and microbiological qualities. According to organoleptic test, the overall highest score was observed in sample B (84.37±1.64) and the lowest score was found in sample D (75.0±1.41). In all levels of replacement increased fat, carbohydrates, ash and total solids were obtained, while moisture and protein content were significantly decreased in Dahi samples. Acidity and pH of all the treatments were significantly influenced and ranged from 0.65 to 0.73% and 4.21 to 4.57, respectively. Ash content of all samples was not significantly increased. Total viable count of reconstituted Dahi samples (B, C and D) was significantly increased. It could be concluded that 10 and 20 % replacement of reconstituted skim milk with coconut milk for the manufacture of Dahi was acceptable and reduced the production cost, but 10% replacement was better in compare to others, according to organoleptic, chemical and microbiological analysis. DOI: http://dx.doi.org/10.3329/bjas.v43i3.21653 Bang. J. Anim. Sci. 2014. 43 (3): 218-223